Curriculum Integration for Medical and Dental Students - Reddy, Rajeshwar; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2021)
Many medical and dental colleges have been following a traditional curriculum which is characterized by a discipline/subject wise model, with high degree of division of different subjects into pre-clinical, para-clinical, and clinical branches, without any correlation between the different subjects and topics. As a result, the knowledge gained by students becomes irretrievable and inadequate to apply in clinical situations. Lack of integrated approach to different subjects, during learning period, results in bringing out medical graduates lacking holistic approach toward the patients and the community while practicing medicine. Therefore, there is a need for a revision in medical education, not only in terms of the changes in our knowledge base, but also in terms of the regarding patients, medical practitioners and society in general. Integrated curriculum seeks to break down the barriers between the subject areas i.e., basic and clinical sciences, in order to promote acquisition, retention, and progressive development of knowledge and skills, and facilitate applications of principles and concepts to understand problems and develop problem solving skills. It views learning and teaching in a holistic way and reflects the real world, which is interactive, and helps students to apply their knowledge to their work and to their personal development. This article pertaining to the discipline of medical education makes an attempt to review and discuss the various types of curriculum and its integration for MBBS and BDS students.